Space creation for a missing central incisor using functional and fixed appliances - Waeil Batwa; Ibtesam Alzain (Wolters Kluwer Medknow Publications, 2018)
Children with an overjet of more than 6 mm are three times more likely to receive trauma to their upper incisors than children with an average overjet. This could be complicated with avulsion of permanent incisor and with space loss for the tooth. Functional appliances are usually used to treat Class II skeletal pattern and increased overjet in growing patients. The following is a case in which the Twin Block functional appliance was used, while its classic design was modified to treat a Class II skeletal problem and to open a space for a missing maxillary central incisor.